Examining awareness of privilege among midwestern college students: An analysis of race/ethnicity, gender, and religion. Issue 1 (1st November 2022) - Todd, Nathan R.; Blevins, Emily J.; Yi, Jacqueline; Boeh Bergmann, Brett A.; Meno, Camarin G.
Abstract: Dominant group members often are not aware of the privileges they benefit from due to their dominant group membership. Yet individuals are members of multiple groups and may simultaneously occupy multiple categories of dominance and marginality, raising the question of how different group memberships work in concert to facilitate or inhibit awareness of multiple forms of privilege. Examining awareness of privilege is important as awareness may be linked to action to dismantle systems of privilege that maintain oppression and inequality. Grounded in intersectional scholarship, in this study we examined how occupying intersecting categories of race/ethnicity, gender, and religion corresponded to an awareness of White, male, and Christian privilege. In a sample of 2321 Midwestern college students, we demonstrated that students from marginalized groups broadly reported greater awareness of all forms of privilege than students from dominant groups, and the difference between marginalized and dominant groups was most pronounced when the specific group category (e.g., gender) aligned with the type of privilege (e.g., male privilege). We also tested interactions among race/ethnicity, gender, and religion, only finding an interaction between race/ethnicity and religion for awareness of White and male privilege. These findings helped to clarify that multiple group memberships tended to contribute to awareness as multiple main effects rather than as multiplicative. Finally, we examined mean differences among the eight intersected groups to explore similarities and differences among groups in awareness of all types of privilege. Taken together, these findings quantitatively demonstrate the ways in which group memberships work together to contribute to awareness of multiple forms of privilege. We discuss study limitations and implications for community psychology research and practice. Highlights: We tested how race/ethnicity, gender, and religion related to awareness of privilege. We examined awareness of White, male, and Christian privilege as three types of privilege. For each privilege type, we tested main and interactive effects of race/ethnicity, gender, and religion. We examined similarities and differences in privilege awareness across intersected groups. We show how group memberships work together to contribute to awareness of three types of privilege.